A Challenging Cutaneous T-Cell Lymphoma. (January 2016) - Khadhar, Aida; Chelly, Ines; Zehani, Alia; Litaiem, Noureddine; Zaraa, Ines; Azouz, Haifa; Bellil, Khadija; de Mascarel, Antoine; Haouet, Slim; Kchir, Nidhameddine
Abstract : Abstract: Cutaneous peripheral T-cell lymphomas not otherwise specified (CPTL-NOS) are rare neoplasms accounting for just 2% of cutaneous peripheral T-cell lymphomas (CPTL). Only very few case series have been reported. They represent a phenotypically and prognostically heterogenous group of CPTL that do not fit into any of CPTL well-defined subtypes. The authors report a case of a 64-year-old man with simultaneous plaque-like lesions and disseminated nodules growing rapidly on the face, trunk, and extremities over a 6-month period. There was no a history of preceding patches, erythematous plaques, rash, or pruritic lesions. These lesions were extending over 80% of the skin surface. Histopathologic analysis revealed dense diffuse infiltrates composed of mostly medium-sized to large lymphoid cells throughout the entire dermis without epidermotropism. Neoplastic cells were atypical with markedly pleomorphic nuclei. Immunohistochemistry showed that the tumor cells were positive for CD3, CD4, and CD5 with a loss of CD7. They were negative for CD20, CD8, CD56, CXCL13, PD1, TIA-1, granzyme-B, perforin, CD25, and CD30. The proliferative fraction was low, with MIB-1 labeling less than 10% of cells. The authors diagnosed the patient with primary CPTL-NOS. Despite the rarity of these tumors, clinicians as well as dermatopathologists and pathologists should be familiar with these rare CPTL especially because most of these lymphomas have an aggressive behavior and exhibit an unfavorable prognosis.